Virtual Psychosocial Therapy for Mental and Psychological Health Recovery during the Covid-19 Pandemic - Sholihin Sholihin; Tria Anisa Firanti; Melania Belqis; Widiya Fara Diba; Shinta Bella (Jurnal Keperawatan, 2022)
For almost 2 years since February 2020 the Indonesian people have lived side by side with Covid-19. In Indonesia itself, various policies have been implemented such as Lockdown, Large-Scale Social Restrictions and Enforcement of Restrictions on Community Activities. These policies are certainly very influential on the economic system, industry, mental health and people's psychology. The World Health Organization (WHO) states that negative effects on mental and psychosocial health need special attention. Virtual Psychosocial Therapy is a virtual-based psychological therapy in an effort to restore mental and psychological health for people affected by Covid-19. This literature review is to identify innovations in virtual-based psychological therapy in efforts to restore mental and psychosocial health during the Covid-19 pandemic. The method used in this research paper is a literature review using the Google Scholar, Scopus, Science Direct database. There are 12 recent articles with the theme of virtual-based psychological therapy that we have reviewed with the year 2020-2021 published. From the results of our review of the 12 articles, there are 4 types of virtual-based psychological therapy, namely telepsychology, telemental, teletherapeutic and Cyber Counseling. The problems regarding psychological disorders experienced by the community are excessive anxiety during the pandemic and boredom as a result of the policies set by the government that require people to carry out almost all of their activities from home. There are 4 types of virtual-based psychological therapy that we have obtained, namely telepsychology, telemental, teletherapeutic and Cyber Counseling, which are carried out virtually by utilizing the development of science and technology through internet network communication media so that it can be done anywhere and anytime with a time agreed upon by the counseling and counselor so that there is no need to meet face-to-face during the Covid-19 pandemic. Virtual-based psychological therapy by utilizing science and technology developments is effective in improving the mental and psychological health status of the community during the Covid-19 pandemic.